Insulin attenuates apoptosis in neuronal cells by an integrin-linked kinase-dependent mechanism. Issue 8 (August 2019) - Tan, Jacqueline; Digicaylioglu, Murat; Wang, Stacy X.J.; Dresselhuis, Jonathan; Dedhar, Shoukat; Mills, Julia
Abstract: Insulin promotes neuronal survival by activating a phosphatidylinositol 3-kinase (PI 3-kinase)/AKT-dependent signaling pathway and reducing caspase activation. We investigated a role for integrin-linked kinase (ILK) in insulin-mediated cell survival in cultured neurons and differentiated R28 cells. We used a serum and depolarization withdrawal model to induce apoptosis in cerebellar granule neurons and a serum withdrawal model to induce apoptosis in differentiated R28 cells. ILK knock-out decreased insulin-mediated protection as did the addition of pharmacological inhibitors of ILK, KP-392 or QLT-0267. Prosurvival effects of insulin were rescued by Boc-Asp (O-methyl)-CH2 F (BAF), a pancaspase inhibitor, in the presence of KP-392. Insulin and IGF-1 decreased caspase-3 activation, an effect that was inhibited by KP-392 and QLT-0267. Western blot analysis indicates that insulin-induced stimulation of AKT Ser-473 phosphorylation was decreased after the ILK gene was conditionally knocked-out, following overexpression of AKT-DN or in the presence of QLT-0267. Insulin and IGF-1 stimulated ILK kinase activity in primary neurons and this was inhibited following ILK-DN overexpression. Western blot analysis indicates that insulin exposure upregulated the expression of the cellular inhibitor of apoptosis protein c-IAP2 in an extracellular matrix-dependent manner, an effect blocked by KP-392. These results indicate that ILK is an important effector in insulin-mediated neuroprotection.